Modern clinical management helps reducing the impact of type 1 diabetes in children. (August 2015) - Scaramuzza, Andrea E.; Zuccotti, Gian Vincenzo
Graphical abstract: Abstract: Type 1 diabetes care may be very costly not only in terms of money but also in terms of psychological and therapeutic acceptance and compliance. Recently, a lot of new technologies have been introduced in the care of patients with type 1 diabetes that should allow them to achieve an improvement in glycemic control, quality of life and above all prevent long-term complications. Combining continuous glucose monitoring (CGM) and continuous subcutaneous insulin infusion (CSII) provides a more useful tool for patients with type 1 diabetes, the sensor-augmented pump (SAP). The aim of the present review is to explore SAP efficacy and safety in young patients with type 1 diabetes. SAP demonstrated increased efficacy in lowering glycated hemoglobin when compared either to multiple daily injections or CSII alone. Its efficacy is positively associated with CGM use, baseline HbA1c and patients' age. According to currently available evidence, SAP seems sufficiently safe, effective and beneficial in improving glycemic control in pediatric patients with type 1 diabetes. Moreover, encouraging results using semi-closed loop systems are emerging, paving the way toward a fully automated artificial pancreas. As pediatric diabetologists we have the duty to offer our patients the best therapeutic option currently available, supported by evidence, to help them gain the best results with the fewest adverse effects (hypoglycemia and/or diabetic ketoacidosis), better if chomping a little piece of dark chocolate.